Analysis of Working Capital Management and Cash Holding on Profitability of Manufacturing Companies Listed in Indonesia Stock Exchange Period 2014 – 2018 - Niko Sianipar; Syamsu Alam; Mursalim Nohong (Magister Management, Hasanuddin University, 2020)
This research aims to analyze the effect of working capital management on the profitability of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018. Working capital management indicators used in this research are the cash conversion cycle (CCC), the inventory conversion period (ICP), the receivable conversion period (RCP), the debt repayment period (PDP), and Cash Holding (CASH). On the other hand, the profitability indicator used in this research is Return On Assets (ROA) The sample data used in this study is taken from the audited financial statements and published on the IDX. According to the sampling technique used in this research, namely purposive sampling, there are 73 companies that fit certain criteria. This research uses descriptive statistics with a quantitative approach and uses time series data regression techniques assisted with the Eviews version 9 program. Hypothesis testing uses F statistical tests, t statistical tests, and coefficient determination with a significance level of 5%. The results of this research indicate the simultaneous independent variable (F-statistic test) affect the profitability (ROA) with a significance level of 0,000. On the other hand, partially (t test statistic) shows CCC and PDP have positive and not significant effect on profitability, ICP has a negative and no significant effect on profitability, RCP has a negative and significant effect on profitability. Meanwhile CASH has a positive and significant effect on profitability.